Scrapie-associated fibrils (SAF) purification method yields amyloid proteins from systemic and cerebral amyloidosis. Issue 5 (May 1986) - Kitamoto, Tetsuyuki; Hikita, Kohtaro; Tashima, Takatoshi; Tateishi, Jun; Sato, Yuji
Abstract : We identified fibrils from non-transmissible systemic and cerebral amyloidosis using the purification method of scrapie-associated fibrils (SAF). The fibrils possessed the same nature of congophilia, filamentous structures and molecular weights as amyloid fibrils, and were resistant to Proteinase K digestion. This SAF method makes for a rapid extraction from amyloid-laden tissues. The method, therefore, may purify nontransmissible amyloids alone or together with SAF proteins.